Hydrogeological Assessment in The Southern Part of Butwal Area, Rupandehi, Nepal - Giri, Suraj; Rijal, Motilal; Adhikari, Drona (Himalayan Journal of Science and Technology, 2022)
Groundwater has been utilized as the major source of water for household, irrigation and industrial purpose. The hydrogeological condition in the Terai region of the Butwal area, Rupandehi district was assessed. The subsurface lithological section and hydro-stratigraphic units of the area within the depth of 80 m were produced using secondary data from borehole lithologs. The study area i.e., quaternary deposit, comprises boulders, cobble, pebble, gravel and another alluvial (river) deposits. Thick and coarse aquifer materials (boulder and gravel) were determined at wells (DW-2,5,8 and 6), that were lying nearby rivers and foothills of Siwalik. While the proportion of finer sediments (sand and clay) was greater in the southern part of the study area.  The aquifers in the study area are delineated as unconfined to confined types which are well-recharged primarily through precipitation and surface runoff in the monsoon period. The application of Duba’s Method for groundwater recharge in the study area shows 44 MCM/year. Though the study area is an urban area, the physicochemical parameters like pH, TDS, DO, EC and temperature range within Nepal’s Drinking Water Standard permissible limits. However, as urbanization grows, the quality and quantity may deteriorate in the future, necessitating the adoption of appropriate and sustainable management techniques to safeguard these groundwater resources.